Biomethane and Biohydrogen from Biowaste /Wastewater - Sriwuryandari, Lies; Sembiring, T. (LIPI Press, 2014)
The production of renewable energy from biowaste or liquid biowaste in anaerobic condition by the activity of methanogenic archeabacteria in the central role is known as biomethanation. However, at the high concentration of loading rate of the process, related with the sensitivity of methanogens to the environmental shift, such as pH, heavy metals, sulfide, and hydrogen partial pressure, as well as the need of the methanogens to the strict anaerobic conditions, the methane production often was disturbed, even failed. This is one problem in the biowaste and liquid biowaste conversion into methane. Study on the fermentation process of biowaste/liquid biowaste into hydrogen is an attractive solution on the solving of environmental pollution and the need of energy. The complexity of the hydrogen production is seemly less than that of biomethanation due to the needs of the active microorganisms in the processes.